Maternal Use of Selective Serotonin Reuptake Inhibitors and Risk of Miscarriage – Assessing Potential Biases. Issue 1 (10th November 2014) - Johansen, Rie Laurine Rosenthal; Mortensen, Laust Hvas; Andersen, Anne‐Marie Nybo; Hansen, Anne Vinkel; Strandberg‐Larsen, Katrine
Abstract Background The use of selective serotonin reuptake inhibitors (SSRIs) during pregnancy has been associated with miscarriage, but the association may be biased by maternal mental illness, lifestyle and exposure misclassification. Methods A register study on all pregnancies in Denmark between 1996 and 2009 was conducted using individualised data from the Danish National Patient Register, the Medical Birth Register, the Danish Psychiatric Central Register, the Danish National Prescription database and the Danish National Birth Cohort (DNBC). Results A total of 1 191 164 pregnancies were included in the study, of which 98 275 also participated in the DNBC. Pregnancies exposed to SSRIs during or before pregnancy were more likely than unexposed pregnancies to result in first trimester miscarriage, hazard rate (HR) = 1.08 [95% confidence interval (CI) 1.04, 1.13] and HR = 1.26 [95% CI 1.16, 1.37], respectively. No difference was observed for second trimester miscarriage. SSRI‐exposed pregnancies without a maternal depression/anxiety diagnosis from a psychiatric department were less likely to result in first trimester miscarriage than unexposed pregnancies with a diagnosis, HR = 0.85 [95% CI 0.76, 0.95]. SSRI‐exposed pregnancies were characterised by an unhealthier maternal lifestyle and mental health profile than unexposed pregnancies, whereas no convincing differences were observed between pregnancies exposed to SSRIs during versus before pregnancy. Substantial disagreement was found between prescriptions and self‐reported use of SSRIs, but it did not affect the estimated hazard ratios. Conclusion Confounding by indication and lifestyle in pregnancy may explain the association between SSRI use and miscarriage.